Selecting a quality smartphone for students’ preference based on Analytical Hierarchy Process (AHP) / Nurul Afiqah Ismail, Noor Nadhirah Zarkhsi and Wan Nur Fatin Wan Mahmmud - Ismail, Nurul Afiqah; Zarkhsi, Noor Nadhirah; Wan Mahmmud, Wan Nur Fatin (2023)
Smartphones are nearly a requirement for university students. The study identifies and highlights the aspects that students evaluate when buying smartphones. They always use smartphones in order to get information that is related to educational purposes and also to download varieties of applications and information on their smartphones. As smartphones have already blended into their lives, some of them have slowly realised that having an overqualified smartphone will not really benefit them as students. Therefore, this study is to assist the student in selecting the best brand of smartphone that will help with their daily life by using the Analytical Hierarchy Process (AHP). It showed that Apple is the best smartphone that meets the criteria that will improve the students' lives. Due to the fact that each person uses their smartphone in a different way, students should concentrate more on the features that are most important to them.